Design for deconstruction using a circular economy approach: barriers and strategies for improvement - Akinade, Olugbenga; Oyedele, Lukumon; Oyedele, Ahmed; Delgado, Juan Manuel Davila; Bilal, Muhammad; Akanbi, Lukman; Owolabi, Hakeem (Taylor & Francis Ltd, 2020)
This study explores the current practices of Design for Deconstruction (DfD) as a strategy for achieving circular economy. Keeping in view the opportunities accruable from DfD, a review of the literature was carried out and six focus group interviews were conducted to identify key barriers to DfD practices. The results of phenomenology reveal 26 barriers under five key barrier categories. The barrier categories to DfD are 'lack of stringent legislation and policies', 'lack of adequate information at the design stage', 'lack of large enough market for recovered components', 'difficulty in developing a business case for DfD', and 'lack of effective DfD tools'. After this, the study identifies the strategies for overcoming these barriers. The paper, therefore, addresses the need for actions within the construction industry to bring DfD to the fore towards achieving the current global sustainability agenda.
Keywords: Building deconstruction sustainability circular economy model; construction and demolition waste; barriers and strategies